2020
DOI: 10.3390/ijms21217946
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tryptophan-Derived AhR Ligands, Kynurenine, Kynurenic Acid and FICZ, on Proliferation, Cell Cycle Regulation and Cell Death of Melanoma Cells—In Vitro Studies

Abstract: Tryptophan metabolites: kynurenine (KYN), kynurenic acid (KYNA) and 6-formylindolo[3,2-b]carbazole (FICZ) are considered aryl hydrocarbon receptor (AhR) ligands. AhR is mainly expressed in barrier tissues, including skin, and is involved in various physiological and pathological processes in skin. We studied the effect of KYN, KYNA and FICZ on melanocyte and melanoma A375 and RPMI7951 cell toxicity, proliferation and cell death. KYN and FICZ inhibited DNA synthesis in both melanoma cell lines, but RPMI7951 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(73 citation statements)
references
References 53 publications
5
57
0
Order By: Relevance
“…Importantly, kynurenic acid also has antiproliferative and antimigratory properties against various types of cancer cells (reviewed in [ 179 ]) by inhibition of signaling pathways (MAPK, PI3K/Akt) and overexpression of cell cycle regulatory proteins (p21Waf1/Cip1) [ 119 , 201 ]. Moreover, a recent study confirmed the biological activity of kynurenic acid towards melanoma A375 and RPMI-7951 cells [ 202 ].…”
Section: The Role Of Tryptophan-derived Ahr Ligands In Skin Homeosmentioning
confidence: 78%
“…Importantly, kynurenic acid also has antiproliferative and antimigratory properties against various types of cancer cells (reviewed in [ 179 ]) by inhibition of signaling pathways (MAPK, PI3K/Akt) and overexpression of cell cycle regulatory proteins (p21Waf1/Cip1) [ 119 , 201 ]. Moreover, a recent study confirmed the biological activity of kynurenic acid towards melanoma A375 and RPMI-7951 cells [ 202 ].…”
Section: The Role Of Tryptophan-derived Ahr Ligands In Skin Homeosmentioning
confidence: 78%
“…However, the direct activity of KYN on cancer cell proliferation has not been fully studied. On the contrary, another tryptophan-derived AhR ligand, KYNA, enzymatically formed from KYN, has antiproliferative and antimigratory properties against various types of cancer cells, including glioma, colon, and renal cancer cells [ 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, recent research has revealed that selected tryptophan-derived AhR ligands, including KYN and KYNA, possess biological activity toward melanoma A375 and RPMI-7951 cells [ 11 ]. The tryptophan metabolites affected DNA synthesis, cell cycle regulators, and cell death of melanoma cells in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the pivotal importance of milk protein in human health, investigating supplementation with AAs (e.g., methionine, lysine) as the main nutrients that can positively stimulate milk protein synthesis in mammary epithelial cells (MEC) has been a priority as of late [ 2 ]. Tryptophan (Trp), known as a conditional EAA [ 3 ], can be supplemented in the diets of animals and humans when targeting maximal production, cell growth, and proliferation [ 4 , 5 , 6 ]. Furthermore, Trp has been widely introduced as a mostly harmless supplement for humans to cope with health issues such as stress and depression.…”
Section: Introductionmentioning
confidence: 99%